Incidence of diverse dsRNA mycoviruses in Trichoderma spp. causing green mold disease of shiitake Lentinula edodes. Issue 19 (22nd September 2016) - Yun, Suk-Hyun; Lee, Song Hee; So, Kum-Kang; Kim, Jung-Mi; Kim, Dae-Hyuk
Abstract : A total of 315 fungal isolates causing green mold disease were collected from contaminated artificial logs and sawdust bags used for cultivating shiitake Lentinula edodes in Korea and were analyzed for the presence of double-stranded RNA (dsRNA). dsRNA, which was purified using dsRNA-specific chromatography and verified by dsRNA-specific RNaseIII digestion, was detected in 32 isolates. The molecular taxonomy of dsRNA-infected isolates indicated that all isolates belonged to the Trichoderma spp.. The number and size of dsRNAs varied among isolates and the band patterns could be categorized into 15 groups. Although there were seven dsRNA groups observed in multiple isolates, eight groups were found to occur in single isolates. The most common dsRNA group, group VI, which contained a band of 10 kb, occurred in 10 isolates encompassing three species of Trichoderma . Partial sequence analysis of two selected dsRNA groups revealed a high degree of similarity to sequences of a RNA-dependent RNA polymerase, hypothetical protein and polyprotein genes of other hypoviruses such as Macrophomina phaseolina hypovirus 1, Trichoderma hypovirus, and Fusarium graminearum hypovirus 2, respectively, indicating the occurrence of mycoviruses in Trichoderma spp.. Northern blot analysis suggested that many different mycoviruses, which have not been identified yet, exist in Trichoderma . Abstract : The prevalence of dsRNA mycoviruses in Trichodesma spp.